2001
DOI: 10.1186/1471-2407-1-16
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of E-cadherin and β-catenin in gastric cancer

Abstract: Background: The E-cadherin-catenin complex plays a crucial role in epithelial cell-cell adhesion and in the maintenance of tissue architecture. Perturbation in the expression or function of this complex results in loss of intercellular adhesion, with possible consequent cell transformation and tumour progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
44
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 25 publications
7
44
0
2
Order By: Relevance
“…We observed that a-and b-catenin appeared in a granular cytoplasmic pattern in tumors. Our data are in partial agreement with the aberrant expression and localization of b-catenin that has been reported in a variety of human cancers including colon, 36 liver, 37 stomach, 38 pancreas, 39 bone, 40 and thyroid. 41 Reports that have studied the expression of b-catenin in human lung cancer remain controversial.…”
Section: Discussionsupporting
confidence: 80%
“…We observed that a-and b-catenin appeared in a granular cytoplasmic pattern in tumors. Our data are in partial agreement with the aberrant expression and localization of b-catenin that has been reported in a variety of human cancers including colon, 36 liver, 37 stomach, 38 pancreas, 39 bone, 40 and thyroid. 41 Reports that have studied the expression of b-catenin in human lung cancer remain controversial.…”
Section: Discussionsupporting
confidence: 80%
“…As a key regulator of the differentiated epithelial phenotype, E-cadherin plays a critical role in the suppression of tumour invasion, and its function is required for the maintenance of stable adherens junctions and epithelial cell polarity (Takeichi, 1991;Perez-Moreno et al, 2003). Occurrence of altered E-cadherin expression has been correlated with dedifferentiation, increased risk of local invasion and metastatic disease, and recurrence and poor prognosis in a variety of carcinomas, for example, breast, uterine cervix, or gastric carcinomas (Moll et al, 1993;Fujimoto et al, 1997;Jawhari et al, 1997;Jeffers et al, 1997;Huiping et al, 2001). Previous studies have shown that reduced expression of E-cadherin in ovarian cancer is associated with the invasive phenotype, advancing tumour stage, lower 5-year survival rate, and poor recurrence-free survival (Faleiro-Rodrigues et al, 2004;Imai et al, 2004;Marques et al, 2004;Voutilainen et al, 2006) but not much is known about the underlying mechanisms of E-cadherin downregulation.…”
mentioning
confidence: 99%
“…[15][16][17][18][19] Indeed, downregulation or abnormal expression of E-cadherincatenin proteins has been reported to be associated with poor histologic differentiation of tumors, increased risk of peritoneal metastasis, and poor patient outcome in ovarian cancer as well as in various solid cancers at other primary sites. [19][20][21][22][23][24] Although, for disease progression, ovarian cancer cells should require cell motility besides loss of cellto-cell adhesion, the molecular backgrounds underlying this process is still unclear.…”
mentioning
confidence: 99%